2023
DOI: 10.1039/d2ta08365e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bond-mediated pH-universal electrocatalytic hydrogen production by conjugated porous poly-indigo

Abstract: High-performing catalysts for hydrogen evolution reaction (HER) via water electrolysis are of great importance for producing carbon-free green fuels. Compared to the routinely used metal-based systems under acidic conditions, metal-free...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The HER performance was attributed to an intrinsic chemical and electronic coupling, which synergistically enhanced the kinetics of proton adsorption and reduction. Furthermore, Verpoort et al 146 reported a conjugated porous poly-indigo (Ind-CPP) polymer, which exhibited a good HER performance with an overpotential of 359 mV ( η 10 ) in an acidic medium and 364 mV ( η 10 ) in an alkaline medium, respectively. Besides, a Tafel slope of 64 mV dec −1 was calculated for Ind-CPP at pH = 0, which increases to 73 mV dec −1 at pH = 14 (Fig.…”
Section: Metal-free Catalysis For the Hermentioning
confidence: 99%
“…The HER performance was attributed to an intrinsic chemical and electronic coupling, which synergistically enhanced the kinetics of proton adsorption and reduction. Furthermore, Verpoort et al 146 reported a conjugated porous poly-indigo (Ind-CPP) polymer, which exhibited a good HER performance with an overpotential of 359 mV ( η 10 ) in an acidic medium and 364 mV ( η 10 ) in an alkaline medium, respectively. Besides, a Tafel slope of 64 mV dec −1 was calculated for Ind-CPP at pH = 0, which increases to 73 mV dec −1 at pH = 14 (Fig.…”
Section: Metal-free Catalysis For the Hermentioning
confidence: 99%
“…125 Hydrogen, however, is colorless, tasteless and flammable. 126 To ensure reliable utilization of hydrogen, accurate detection of the generation and leakage of hydrogen is necessary. Palladium is a widely used material for hydrogen sensors by dissociative absorption energy.…”
Section: Diverse Energy Applications Of Films With Nanoengineered Sur...mentioning
confidence: 99%